2003
DOI: 10.1038/sj.onc.1206344
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular subtypes of glioblastoma by gene expression profiling

Abstract: Epidermal growth factor receptor (EGFR) overexpression occurs in nearly 50% of cases of glioblastoma (GBM), but its clinical and biological implications are not well understood. We have used Affymetrix high-density oligonucleotide arrays to demonstrate that EGFR-overexpressing GBMs (EGFR+) have a distinct global gene transcriptional profile. We show that the expression of 90 genes can distinguish EGFR+ from EGFR nonexpressing (EGFRÀ) GBMs, including a number of genes known to act as growth/survival factors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
134
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(138 citation statements)
references
References 59 publications
2
134
0
Order By: Relevance
“…Our data suggest that these tumors are somewhat similar to NSCs but more strongly suggest that pediatric astrocytomas and high-grade gliomas are derived from either NSCs or progenitor cells. Previous studies have demonstrated that adult high-grade gliomas can form multiple differentiated cell types (42), and that some cells can form neurospheres with multiple differentiated cell types (40). It is unknown whether the originating cells of PNETs, medulloblastomas and gliomas, may be the same type of cell, such as a NSC, but resulting from different transformation events, or whether the glial tumors arise from a cell at a later stage of differentiation.…”
Section: Discussionmentioning
confidence: 98%
“…Our data suggest that these tumors are somewhat similar to NSCs but more strongly suggest that pediatric astrocytomas and high-grade gliomas are derived from either NSCs or progenitor cells. Previous studies have demonstrated that adult high-grade gliomas can form multiple differentiated cell types (42), and that some cells can form neurospheres with multiple differentiated cell types (40). It is unknown whether the originating cells of PNETs, medulloblastomas and gliomas, may be the same type of cell, such as a NSC, but resulting from different transformation events, or whether the glial tumors arise from a cell at a later stage of differentiation.…”
Section: Discussionmentioning
confidence: 98%
“…Several works (Sallinen et al, 2000;Khan et al, 2001;Ramaswamy et al, 2001;Rickman et al, 2001;Agrawal et al, 2002;Kim et al, 2002;Veer et al, 2002;Vijver et al, 2002;Boom et al, 2003;Godard et al, 2003;Hunter et al, 2003;Mischel et al, 2003;Nutt et al, 2003;Shai et al, 2003;Sorlie et al, 2003;Freije et al, 2004;Mischel et al, 2004;Hoelzinger et al, 2005;Liang et al, 2005;Nigro et al, 2005;Rich et al, 2005;Somasundaram et al, 2005;Wong et al, 2005) showed the usefulness of utilizing methods of analysis of multiple forms of data including both clinical and multiple genes, to achieve a more precise discrimination of outcomes for individual patients. The same logical use of multiple forms of data and methods of analysis has been applied in the present study to accurately achieve better classification and prediction of glioma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, developed microarray technology has permitted development of multi-organ cancer classification including gliomas (Ramaswamy et al, 2001;Rickman et al, 2001;Kim et al, 2002;Hunter et al, 2003;Mischel et al, 2004), identification of tumor subclasses (Khan et al, 2001;Mischel et al, 2003;Shai et al, 2003;Sorlie et al, 2003;Liang et al, 2005;Nigro et al, 2005;Wong et al, 2005), discovery of progression markers (Sallinen et al, 2000;Agrawal et al, 2002;van de Boom et al, 2003;Godard et al, 2003;Hoelzinger et al, 2005;Rich et al, 2005;Somasundaram et al, 2005) and prediction of disease outcomes (van't Veer et al, 2002;van de Vijver et al, 2002;Nutt et al, 2003;Freije et al, 2004). Unlike clinicopathological staging, molecular staging can predict long-term outcomes of any individual based on gene expression profile of the tumor at diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…23 As these genetic lesions regulate biological and clinical behaviors of tumor cells, the resultant disrupted signaling pathways represent attractive targets for therapy. 24 The aim of this study was to elucidate whether PTEN status could alter cellular responses to IR using five different glioma cell lines. We found that PTEN-deficient U87, U373, and U252 glioma cells, which have an active AKT signaling pathway because of the absence of PTEN, entered senescence following IR exposure.…”
Section: Discussionmentioning
confidence: 99%